Review of the literature on the use of social media by people with traumatic brain injury (TBI). (19th May 2015) - Brunner, Melissa; Hemsley, Bronwyn; Palmer, Stuart; Dann, Stephen; Togher, Leanne
Abstract: Purpose : To review the literature relating to use of social media by people with a traumatic brain injury (TBI), specifically its use for social engagement, information exchange or rehabilitation. Method : A systematic review with a qualitative meta-synthesis of content themes was conducted. In June 2014, 10 databases were searched for relevant, peer-reviewed research studies in English that related to both TBI and social media. Results : Sixteen studies met the inclusion criteria, with Facebook™ and Twitter™ being the most common social media represented in the included studies. Content analysis identified three major categories of meaning in relation to social media and TBI: (1) risks and benefits; (2) barriers and facilitators; and (3) purposes of use of social media. A greater emphasis was evident regarding potential risks and apparent barriers to social media use, with little focus on facilitators of successful use by people with TBI. Conclusions : Research to date reveals a range of benefits to the use of social media by people with TBI however there is little empirical research investigating its use. Further research focusing on ways to remove the barriers and increase facilitators for the use of social media by people with TBI is needed. Implications for Rehabilitation: Communication disabilities following traumatic brain injury (TBI) can be wide-ranging in scope and social isolation with loss of friendships after TBI is common. For many people, social media is rapidly becoming a usual part of everyday communication and its use has the potential to increase communication and social participation for people with TBI. There is emerging evidence and commentary regarding the perceived benefits and risks, barriers and facilitators and purposes of use of social media within the TBI population. Risks associated with using social media, and low accessibility of social media sites, form barriers to its use. Facilitators for social media use in people with TBI include training the person with TBI and their communication partners in ways to enjoy and use social media safely. There is minimal rigorous evaluation of social media use by people with TBI and scant information regarding social media use by people with communication disabilities after TBI. Further investigation is needed into the potential benefits of social media use on communication, social participation and social support with the aim of reducing social isolation in people with TBI.